2021
DOI: 10.1017/s0033291721004839
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic and lockdowns on the consumption of anxiolytics, hypnotics and antidepressants according to age groups: a French nationwide study

Abstract: Background Previous studies have shown a negative impact of the COVID-19 pandemic and its associated sanitary measures on mental health, especially among adolescents and young adults. Such a context may raise many concerns about the COVID-19 pandemic long-term psychological effects. An analysis of administrative databases could be an alternative and complementary approach to medical interview-based epidemiological surveys to monitor the mental health of the population. We conducted a nationwide study to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
5
37
0
1
Order By: Relevance
“…France is particularly affected by suicide, with nearly 9,000 suicides per year. Suicide is also the second leading cause of death among young adults (15–24 years old), and the first warning signs have already been reported among this population: the consumption of anxiolytics, antidepressants, and hypnotics has increased during the first year of the COVID-19 pandemic, compared to the five previous years ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…France is particularly affected by suicide, with nearly 9,000 suicides per year. Suicide is also the second leading cause of death among young adults (15–24 years old), and the first warning signs have already been reported among this population: the consumption of anxiolytics, antidepressants, and hypnotics has increased during the first year of the COVID-19 pandemic, compared to the five previous years ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The global upward trends in psychotropic consumption after the start of the COVID-19 epidemic have been verified in several studies [ 25 ], although not all [ 26 ]. The EPIPHARE study, a pharmaco-epidemiological study conducted by French public institutions and including data on the whole French population since 2018, reported changes in outpatient drug consumption and particularly a significant downward trend in the consumption of anxiolytics, hypnotics, and antidepressants until 2019, but which was interrupted in 2020 at the start of the pandemic [ 23 ].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we cannot dismiss the possibility that patients with AN were managed by ambulatory physicians, thereby reducing hospital care. For instance, it has been shown that the prescriptions of psychotropic drugs, such as antidepressants, anxiolytics and hypnotics, increased dramatically during the pandemic nationwide [ 7 , 37 ], suggesting an increase in outpatient versus inpatient care. In addition, we must point out that the study was carried out exclusively on inpatients with AN admitted to general hospital wards, at least initially, which could potentially lead to an underestimation of the number of patients with AN hospitalized exclusively for psychiatric stabilization (i.e., in psychiatric units, which are separate from the other hospital wards).…”
Section: Discussionmentioning
confidence: 99%
“…Although the French authorities actively supported the economy and therefore indirectly limited the risk of an economic recession that may have had additional negative psychological consequences, the national containment measures, which included social distancing, as well as the closure of schools, universities, and “non-essential” workplaces and services, led to social isolation and loneliness for many people. Numerous reports have described the increase in psychological disturbances (i.e., anxiety, depression and self-harming behaviors) that emerged during the COVID-19 crisis [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%